(untitled) (Journal of Dhaka National Medical College & Hospital, 2019)
Background: Succinylcholine is the most commonly used depolarizing muscle relaxant for endotracheal intubation. The most common side effect of succinylcholine is postoperative myalgia which is distressing to the patient. Aim of study: This study was designed to evaluate effectiveness of intravenous magnesium sulfate in reducing the incidence of succinylcholine induced postoperative myalgia. Materials and Methods: 80 (Eighty) adult patients of ASA grade I and II of both sexes for elective surgery under general anesthesia were randomly allocated into two equal groups, magnesium sulfate group and normal saline as placebo group. The patients of magnesium sulfate group were pretreated with magnesium sulfate 40 mg/kg body weight in 10 mL volume, while patients of normal saline (placebo) group were given isotonic saline 0.9% in the same volume (10 mL) intravenously slowly over 10 minutes. Premedication was done by injecting 1.5 mg/kg of fentanyl in iv route. Thereafter, anaesthesia was induced in all patients, by 2 mg/kg of propofol intravenously. Following the loss of eyelid reflex, 1.5 mg/kg of succinylcholine was injected intravenously as a muscle relaxant and then the patients were intubated. The incidence and severity of myalgia were assessed by a blinded observer 24 hours after surgery. Results: Postoperative myalgia recorded immediately in the postoperative ward and upto 48 hours of postoperative period. Postoperative myalgia were recorded in magnesium sulfate group with 15 (37.5%) patients and 27 (67.5%) patients in normal saline (placebo) group respectively which was statistically significant. Conclusion: Pretreatment with intravenous Magnesium sulfate 40 mg/kg reduces the incidence of succinylcholine-induced postoperative myalgia using Propofol as induction agent. J. Dhaka National Med. Coll. Hos. 2019; 25 (02): 18-21